Voluntary Disclosure and Capital Market Assignment Efficiency - Hossien Karbasy Yazdy; Yadollah Noorifard; Taher Mohamadshrefy (پژوهش‌های تجربی حسابداری, 2015)
Quality of the economic transformation of savings into investment is determinant of economic growth and the more investors are informed, the higher quality investment they have. Improvements in quality and level of disclosure cause investors to be more informed of investees' specifications and power and thus promote investment quality and market efficiency. Disclosure quality affects the Stock Exchange efficiency and investment quality. In Iran, improvement of privatization has increased the importance of assignment efficiency and disclosure. This study is aimed to investigate the effect of voluntary disclosure on Assignment efficiency. The sample consists of 136 firms listed in TSE for the period from 2004 to 2010. Data is analyzed by stepwise regression and panel data model. The results show that the voluntary disclosure has a significant positive relation with assignment efficiency but control variables (size, profitability and growth) have a significant negative relation with assignment efficiency.